Heterogeneous clinical spectrum of interstitial lung disease in patients with anti-EJ anti-synthetase syndrome: a case series. Issue 9 (September 2016) - Giannini, Margherita; Notarnicola, Antonella; Dastmalchi, Maryam; Lundberg, Ingrid; Lopalco, Giuseppe; Iannone, Florenzo
Abstract Auto-antibodies against aminoacyl-tRNA-synthetases (anti-ARS Abs) represent the hallmark of the anti-synthetase syndrome that is defined as the clinical association of fever, Raynaud's phenomenon, myositis, interstitial lung disease (ILD), arthritis and mechanic's hands. Recently, differences in clinical features depending on specific anti-ARS Abs have been reported. We describe three cases of anti-EJ (anti-glycyl) antibody-positive patients presenting with ILD as a common feature, but with heterogeneous histopathological and radiographic patterns and with different responses to treatment. Relapsing-remittent fever, refractory muscle involvement and seronegative arthritis were also striking clinical manifestations.